Liberal democracy and the social acceleration of time - Scheuerman, William E. (Johns Hopkins Univ. Press, 2004)
"In Liberal Democracy and the Social Acceleration of Time, William E. Scheuerman offers an assessment of the implications of social and technological celerity in the operation of liberal democracies. Specifically, he asks, what is acceleration's main impact on the traditional, liberal, democratic model of the separation of powers?" "According to Scheuerman, high speed has created an imbalance. The executive branch was intended to react with dispatch; by contrast, legislatures and the courts were designed to be more deliberate and thoughtful. While this system of checks and balances was effective in the age of horse and buggy, Scheuerman argues that the very features that were these institutions' strengths may now be liabilities. Throughout this book, Scheuerman offers a constructive critique that articulates ways in which "liberal democracy might be recalibrated in accordance with the tempo of modern society.""--BOOK JACKET.